2022
DOI: 10.1016/j.aninu.2021.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Different dietary protein sources influence growth performance, antioxidant capacity, immunity, fecal microbiota and metabolites in weaned piglets

Abstract: The inclusion of high-quality proteins are commonly used in swine production. Our research investigated the effects of hydrolyzed wheat protein (HWP), fermented soybean meal (FSBM), and enzyme-treated soybean meal (ESBM) on growth performance, antioxidant capacity, immunity, fecal microbiota and metabolites of weaned piglets. A total of 144 piglets (weaned at 28 d) were allotted to 3 dietary treatments with 6 replicate pens per treatment and 8 piglets per pen. This study included 2 periods: d 0 to14 for phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 50 publications
2
29
0
Order By: Relevance
“…The typical nutritional approach is to formulate diets by utilizing various feed ingredients with highly digestible and palatable ingredients containing functional amino acids, as well as supplemented with additives [3]. A recent report has demonstrated that a highly digestible protein ingredient shows effects against antioxidant and antiinflammation mechanisms, while modulation function is beneficial for gut microbiome [4]. However, the shortage of plant-based protein resources has been the major limiting factor in driving sustainable development in the swine industry, thus, contributing to the search of an alternative feed ingredient.…”
Section: Introductionmentioning
confidence: 99%
“…The typical nutritional approach is to formulate diets by utilizing various feed ingredients with highly digestible and palatable ingredients containing functional amino acids, as well as supplemented with additives [3]. A recent report has demonstrated that a highly digestible protein ingredient shows effects against antioxidant and antiinflammation mechanisms, while modulation function is beneficial for gut microbiome [4]. However, the shortage of plant-based protein resources has been the major limiting factor in driving sustainable development in the swine industry, thus, contributing to the search of an alternative feed ingredient.…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal mucosal barrier function plays a crucial role in maintaining intestinal morphology and homeostasis by preventing the invasion of pathogens and other harmful substances ( 27 , 30 , 31 ). Intestinal permeability has been correlated with some serum parameters, such as D-lactate and DAO ( 9 ). Weaning is a stressful event that directly damages intestinal integrity, increased the serum concentrations of D-lactate, DAO and 5-HT compared with suckling treatment, moreover, soy protein antigens glycinin and β-conglycinin can aggravate this weaning stress through increasing even more D-lactate, DAO and 5-HT than that in weaned piglets without soy protein antigens consumption ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is speculated that feed digestibility and intestinal homeostasis are modulated concomitantly when dietary protein sources are changed. Previous research which concerned more effect of different plant-based sources on intestinal microbiota showed that piglets fed 15.1 and 7.8% ESBM during two experimental phases had higher fecal alpha diversity compared with pigs fed equal amount of hydrolyzed wheat protein and fermented soybean meal, enhanced the relative abundance of Bacteroidetes, Oscillospiraceae , and Christensenellaceae , and decreased the abundance of Clostridiaceae in the feces of weaned pigs ( 9 ). Another study demonstrated that all of the differently treated SBMs which replacing half of dietary fishmeal increased the fecal Lactobacillus counts, while the Escherichia coli counts were not affected compared with the fish meal treatment ( 13 ).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations